2017
DOI: 10.1002/mgg3.303
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed chromosome segregation and multipolar spindle formation in a patient with CHAMP 1 mutation

Abstract: BackgroundPatients with intellectual disability (ID) typically exhibit significant defects in both intelligence and adaptive behavior. Aberration of several genes involved in proper progression of mitosis has been reported to underlie ID. Here, we report a new patient with a novel mutation of CHAMP1.MethodsWhole exome sequencing (WES) analysis was performed. We isolated lymphoblast cells from the CHAMP1 patient and observed chromosome segregation.ResultsWe identified a de novo frameshift mutation in CHAMP1. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…One patient in Tanaka et al's 4 study had generalized seizures that started at the age of 3 years and were adequately treated with levetiracetam. Isidor et al 5 and Okamoto et al 6 have also reported one patient with epilepsy, each.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One patient in Tanaka et al's 4 study had generalized seizures that started at the age of 3 years and were adequately treated with levetiracetam. Isidor et al 5 and Okamoto et al 6 have also reported one patient with epilepsy, each.…”
Section: Discussionmentioning
confidence: 97%
“…Okamoto et al 6 have recently reported a novel patient with a CHAMP1 mutation who had feeding difficulties, failure to thrive, delayed motor development, severely delayed acquisition of language skills, and intellectual disability. This patient showed spasticity of lower extremities, like the second patient we presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients have normal or nonspecific radiographs, while others exhibit slightly delayed myelination, cerebral atrophy and a decreased white matter volume (6,(12)(13)(14). For the patient of the present study, the bilateral lateral ventricular enlargement appeared to be nonspecific, and no abnormalities in the brain parenchyma were identified.…”
Section: Discussionmentioning
confidence: 49%
“…As a result, GDD/ID with speech delay, motor developmental delay and facial anomalies were observed in all patients, as well as hypotonia (17/18), abnormal muscular tone (16/18), vision damage (15/18), abnormal behaviors (14/18) and reproductive issues (13/18) were quite common in patients with MRD40, while seizures (4/18), abnormal hearing (3/18) and spasticity (4/18) were less prevalent phenotypes. The clinical features of the above-mentioned patients are listed in Table I (6,(12)(13)(14). In addition, all identified mutations in the CHAMP1 gene in patients diagnosed with MRD40 are truncating (nonsense or frameshift) mutations (Table II).…”
Section: Literature Reviewmentioning
confidence: 99%